Spatial memory deficits initiated by agroclavine injection or olfactory bulbectomy in rats are characterized by different levels of long-term potentiation expression in the hippocampus. (1st December 2020) - Vorobyov, Vasily; Medvinskaya, Natalia; Deev, Alexander; Sengpiel, Frank; Bobkova, Natalia; Lunin, Sergey
Abstract: Aim: To clarify whether long-term potentiation (LTP) is the mechanism underpinning mnemonic processes. Mathrials and methods: We studied LTP in hippocampal slices from rats whose spatial memory deficit was produced by either olfactory bulbectomy (OBX) or pretreatment with an ergot alkaloid, agroclavine. OBX is accompanied by cholinergic system inhibition whereas agroclavine predominantly activates dopaminergic mediation. The both have been shown to be involved in learning/memory and LTP mechanisms. Results: In OBX- vs. sham-operated rat, we have revealed significant reduction of LTP in hippocampal CA1 region. In contrast, no LTP differences in agroclavine- vs. vehicle-treated rats were observed. Conclusions: These results demonstrate that LTP expression in the hippocampus is dependent on the origin of spatial memory impairment. Furthermore, they suggest that pharmacological and neurodegenerative models of AD might be useful approach for discovery of both AD mechanisms and mixed pathology dementias.